PERAN PEREMPUAN NELAYAN DALAM PRODUKSI DAN DISTRIBUSI HASIL LAUT - DINI SAPUTRI (Departemen Sosiologi Universitas Sumatera Utara, 2012)
ABSTRACT : Fisherwomen's Village is a traditional fishing Percut who still use the traditional way to capture the sea. The main livelihoods (livelihood) in the village are dependen